Ankle laxity and instability in collegiate swimmers - Hsu, C.; Schon, J.; Genovese, T.; McInnis, K. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Ankle flexibility is important in maximizing a swimmer`s kicking speed. The effects of increased ankle flexibility in swimmers has not been documented in the literature. The goal of this study is to evaluate ankle laxity, flexibility, and instability in college swimmers compared to control runners.